O ecossistema empreendedor de Belo Horizonte: análise do caso San Pedro Valley - Helena Carneiro Baeta Pereira (2017)
Entrepreneurship and startup companies are a much-addressed theme currently, and the city of Belo Horizonte is constantly shown as a reference to the subject in the Brazilian context. The objective of this study is to analyze the entrepreneurial ecosystem of startups of Belo Horizonte, according to the pillars pointed by the ecosystem literature as structures that compose these environments. The ecosystem approach to entrepreneurship as a theme changes the focus of traditional studies that address the profile and characteristics of the entrepreneur figure as determinants for the development of the entrepreneurial activity. Five were the pillars chosen from the models of Gnyawali and Fogel (1994), Isenberg (2010; 2011) and Foster (2013): Public policy, Financing and funds, Entrepreneurial culture, Support systems and Human resources. This was done through a descriptive case study and qualitative approach. Data was collected from semistructured interviews with 15 actors, among them entrepreneurs, investors and government representatives, with content analysis used to analyze the data. The most positive and influential pillars in the ecosystem were Those of Support system and Entrepreneurial culture, both supported by the community of entrepreneurs formed by the San Pedro Valley. Pillars Human resources and Public policy have been identified as pillars that need further development in this ecosystem. As far as Public Policy is concerned, the ecosystem suffers from the lack of policy aimed specifically at startups and their dynamic business model. The Human Resources pillar needs to develop Entrepreneurship education in the region, since this is almost absent in teaching institutions from the ecosystem. Consequently, the importance of addressing the entrepreneurial ecosystem of startups in Belo Horizonte, is to increasingly support the development and growth of the startups inserted in the Entrepreneurial ecosystem and make it more representative for the local economy